The mechanical properties of surfactant corrosion inhibitor films by AFM measurements - Xiong, Y.; Pailleret, A.; Kinsella, Brian; Nesic, S. (2011)
Surfactant molecules are commonly used to prevent corrosion of steel by acid producing gases such as CO 2 and H 2 S. The mechanical properties of corrosion inhibitor films formed by tall oil fatty acid (TOFA) imidazolium chloride on mica at 0.5 and 2 times the critical micelle concentration (CMC) were studied using atomic force microscopy (AFM). Film thickness was determined by measuring the depth in an area where the inhibitor molecules were removed by scratching with the AFM tip. Internal structures were resolved by comparing film thickness to molecular length. The kinetics of molecular re-adsorption or film formation was also studied using the scratching technique. The vertical force to penetrate the inhibitor films was dependent on film thickness. Forces of 0.3 and 0.8 MPa were determined for mono and bi-molecular layer films of 2 and 4 nm thick respectively. The lateral force to remove inhibitor molecules from the surface was measured at 14-15 MPa, i.e. over one order of magnitude higher. The measurements suggest that inhibitor molecules would not be removed from steel pipe surfaces by the force of fluid flow alone.